2022
DOI: 10.3389/fsurg.2022.946610
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for the prediction of acute kidney injury in patients after cardiac surgery

Abstract: Cardiac surgery-associated acute kidney injury (CSA-AKI) is the most prevalent major complication of cardiac surgery and exerts a negative effect on a patient's prognosis, thereby leading to mortality. Although several risk assessment models have been developed for patients undergoing cardiac surgery, their performances are unsatisfactory. In this study, a machine learning algorithm was employed to obtain better predictive power for CSA-AKI outcomes relative to statistical analysis. In addition, random forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In contrast to some other studies, Random Forest (RF), a widely used ensemble model, has been shown to perform well in certain contexts. For instance, in Xue et al (2022), RF achieved high accuracy, AUC, and Brier scores of 0.822, 85.8%, and 0.137, respectively, suggesting its efficacy for predicting length of stay in hospital patients. These findings highlight the importance of carefully selecting the appropriate machine learning algorithm based on the specific data and problem being addressed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to some other studies, Random Forest (RF), a widely used ensemble model, has been shown to perform well in certain contexts. For instance, in Xue et al (2022), RF achieved high accuracy, AUC, and Brier scores of 0.822, 85.8%, and 0.137, respectively, suggesting its efficacy for predicting length of stay in hospital patients. These findings highlight the importance of carefully selecting the appropriate machine learning algorithm based on the specific data and problem being addressed.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, the RFC classification prediction model could achieve an AUC value of 0.778 in the test set, while the DCA curve showed a better net benefit than other models. Xue et al [25] have also constructed a CSA-AKI classification prediction model. They found that the random forest model had the best prediction performance and could achieve an AUC value of 0.858 (95% CI: 0.792-0.923).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) are rapidly emerging as transformative tools for diagnosing and managing AKI patients [12][13][14][15][16][17][18][19][20][21]. Compared to traditional methods, ML algorithms can reveal patterns beyond human discernment and enhance SA-AKI prediction accuracy by analyzing vast datasets [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%